PENINGKATAN KREATIVITAS BELAJAR ANAK USIA DINI MELALUI TEKNIK KOLASE BERBASIS SAINTIFIK - Nada, Amalia Khoirun; Hafni, Nurlaili Dina (Alzam: Journal of Islamic Early Childhood Education, 2022)
Abstract: The research in this thesis is motivated by the low creativity ability of children at RA Roudlotul Jannah Kepohbaru Bojonegoro, creativity is the result of interaction between individuals and their environment, the ability to make new combinations, based on data, information, or elements that already exist or are known previously. The purpose of this study was to increase the creativity of group B children at RA Roudlotul Jannah Kepohbaru Bojonegoro through scientific-based collage techniques into an interesting work. This research uses classroom action research (CAR) which consists of four stages of research, namely: observation, planning, implementation and reflection stages. The implementation of the action consists of 2 cycles and 1 RPPH in each cycle. Collecting research data through observation using documentation techniques. Data analysis used qualitative and quantitative analysis techniques. The results of this study indicate that children's creativity increases after taking action through collage techniques using natural materials with a scientific approach. Can be concluded that. In the pre-cycle the child's ability is 15.38%, then the first cycle is 30.76% and in the second cycle is 92.30%.